O Acúmulo de macronutrientes em bulbos de cebola em função de épocas de aplicação de enxofre em condição tropical de baixa altitude - Kiara Barros Milhomens, Kellen; Borges de Oliveira, Liomar; Torquato Tavares, Aline; Neto, João; Pereira de Sousa, Adila; Pereira Teles, Simone; Thalia Prolo, Tamara; Rodrigues do Nascimento, Ildon (Comunicata Scientiae, 2023)
The amount of nutrients extracted by the bulbs represents an important component of nutrient removal from the soil, and its evaluation should be used to define the amount of nutrients to be replenished in the soil, through fertilization programs. The objective of the present study was to verify the accumulation of nutrients in onion bulbs due to the application of sulfur in different phenological stages. The experiments were carried out in a completely randomized design, in a 2 x 5 x 2 factorial scheme, with two cultivars (Dulciana and Vulkana), five S application times (control, at transplanting, at 6 to 7 leaves, at differentiation, and at bulbification) and 2 years of cultivation, with four replicates. After curing, ten bulbs were selected from each treatment, one per random repetition of each commercial plot formed by 20 bulbs from the field experiment, which were identified and taken to a nutrient analysis laboratory. Subsequently, the amount accumulated in the bulb of the content of each nutrient in the plant tissue was determined. Fertilization with sulfur promotes greater accumulation of K and N. The order of nutrient extraction in the presence of sulfur was K> N> P> S> Ca> Mg. The largest accumulations of sulfur in the bulb occurred when applied at the bulbification stage for both cultivars.